(untitled) (Orfeu, 2019)
This paper presents the articulation between three philosophical concepts as operators of musical creation in the scope of both musical composition and performance. This is a retrieval that philosopher Gilles Deleuze makes after the concepts of complicatio, explicatio and implicatio from Giordano Bruno and other philosophers that preceded him. From this framework, this paper presents how these concepts can elucidate the issue of continuity in the recently produced musical discourse, with emphasis on the Brazilian repertoire of the last ten years. Thus, the objective is not only to conduct a conceptual discussion, but mainly the glimpse of creative solutions for Contemporary music, relying on the authors’ own experiences as examples of their applicability.